CARDIOLOGY PUBLICATIONS – SUMMARY AND COMMENTS - A. A. Aleksandrovskyi; A. A. Usanova; A. V. Zor’kina; E. V. Kolpakov; E. P. Brodovskaya (Российский кардиологический журнал)
Some typical limitations of the publications in selected Russian cardiology journals are analysed, and the potential methods to resolve these limitations are discussed.